Efektifitas Kangaroo Mother Care (KMC) terhadap Perubahan Suhu dan Berat Badan BBLR di RSUD Pandan Arang - Wahyu Dwi Agussafutri; Eni Rumiyati; Yunita Wulandari (LPPM Universitas Muhammadiyah Riau, 2022)
Low birth weight babies (LBW) are more often problematic because of difficulty maintaining body temperature due to a lack of subcutaneous fat, a large skin surface area to body weight ratio, and reduced heat production due to insufficient brown fat. One of the treatments for LBW is the Kanggoro Mother Care (KMC) method, in which the baby gets warmth and is closer to the mother. The purpose of this study was to determine the effectiveness of implementation (KMC) on changes in body temperature and body weight of LBW. This type of research is quasy experiment. The experimental group in this study there was 1 group that was given an intervention of KMC management, where the body temperature and weight of the baby would be measured before and after the intervention. The data analysis method used is the Wilcoxon test. The results of the statistical test showed that before and after the implementation of KMC, the p value for temperature changes was 0.001 and the p value for weight gain in LBW was 0.022. The conclusion of this study is that KMC is effective against changes in temperature and weight of LBW infants.